Determinants Of Interest To Pay Zakat Through Sharia Mobile Banking - Alfadri, Ferri; Yarham, M; Siregar, Ardiansyah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The bank provides zakat payment services through mobile banking to meet the needs of conducting banking transactions. The people of the new Sitamiang sub-district, Padangsidimpuan City, still do not use the mobile banking application . The purpose of this study was to determine the interest in paying zakat through mobile banking based on perceptions of convenience, perceived usefulness, perceptions of trust in the people of Sitamiang Baru Village, Padangsidimpuan City. This research is a quantitative research. The data source used is primary data. The data collection technique used is a questionnaire with a sample of 98 people. Data processing using SPSS 25 application. The analysis technique used is multiple linear regression analysis. Partial research results states that the convenience variable has no effect on the interest in paying zakat through mobile banking . Usefulness has no effect on interest in paying zakat through mobile banking. Trust has an effect on interest in paying zakat through mobile banking. While the variables of convenience, usability and trust have a simultaneous influence on the interest in paying zakat through mobile banking in the people of Sitamiang Baru Village .Keywords: Interest, Zakat, Mobile Banking, Perception